Novel Approaches to Treat Experimental Pulmonary Arterial Hypertension: A Review. (22nd March 2010) - Umar, S.; Steendijk, P.; Ypey, D. L.; Atsma, D. E.; van der Wall, E. E.; Schalij, M. J.; van der Laarse, A.
Abstract : Background . Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by an increase in pulmonary artery pressure leading to right ventricular (RV) hypertrophy, RV failure, and ultimately death. Current treatments can improve symptoms and reduce severity of the hemodynamic disorder but gradual deterioration in their condition often necessitates a lung transplant. Methods and Results . In experimental models of PAH, particularly the model of monocrotaline-induced pulmonary hypertension, efficacious treatment options tested so far include a spectrum of pharmacologic agents with actions such as anti-mitogenic, proendothelial function, proangiogenic, antiinflammatory and antioxidative. Emerging trends in PAH treatment are gene and cell therapy and their combination, like (progenitor) cells enriched with eNOS or VEGF gene. More animal data should be collected to investigate optimal cell type, in vitro cell transduction, route of administration, and number of cells to inject. Several recently discovered and experimentally tested interventions bear potential for therapeutic purposes in humans or have been shown already to be effective in PAH patients leading to improved life expectation and better quality of life. Conclusion . Since many patients remain symptomatic despite therapy, we should encourage research in animal models of PAH and implement promising treatments in homogeneous groups of PAH patients.